2004
DOI: 10.1111/j.1365-2044.2004.03669.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance for infraclavicular brachial plexus anaesthesia in children

Abstract: SummaryUltrasonography may offer significant advantages in regional anaesthesia of the upper and lower limbs. It is not known if the same advantages demonstrated in adults also apply to children. We therefore performed a prospective, randomised study comparing ultrasound visualisation to conventional nerve stimulation for infraclavicular brachial plexus anasesthesia in children. Forty children scheduled for arm and forearm surgery underwent infraclavicular brachial plexus blocks with ropivacaine 0.5 ml.kg )1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0
17

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(157 citation statements)
references
References 16 publications
5
135
0
17
Order By: Relevance
“…For example, Williams et al 16 reported adequate surgical anesthesia without rescue in 85% and 78% of patients receiving ultrasound and nerve stimulator guided supraclavicular blocks, respectively. Liu et al 17 reported success rates of 73% and 70% for ultrasound and nerve stimulator guided axillary blocks, respectively, and Marhofer et al 18 reported a 100% success rate for pediatric infraclavicular block guided by either technique. Soeding et al 19 compared ultrasound with landmark guidance and reported successful surgical anesthesia in 95% and 90% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Williams et al 16 reported adequate surgical anesthesia without rescue in 85% and 78% of patients receiving ultrasound and nerve stimulator guided supraclavicular blocks, respectively. Liu et al 17 reported success rates of 73% and 70% for ultrasound and nerve stimulator guided axillary blocks, respectively, and Marhofer et al 18 reported a 100% success rate for pediatric infraclavicular block guided by either technique. Soeding et al 19 compared ultrasound with landmark guidance and reported successful surgical anesthesia in 95% and 90% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Уль-тразвуковая навигация и электростимуляция пери-ферических нервов значительно повышают уровень безопасности блокад и успех их выполнения [3,19,20,21,26,36,41].…”
Section: вве дениеunclassified
“…Beş yaş üzeri çocuklarda analjezik ihtiyacı Verbal Pain Scale (VPS, en düşük 0, en yüksek 10 puan) ile değerlendirildi ve her iki skorlamada da 5 puan ve üzerinde 0. Tartışma US'nun son on yılda kullanımın yaygınlaşmasıyla çocuklarda da rejyonal blokların uygulaması artış göstermiştir (8,9). Aslında çocuklarda US teknik olarak erişkinlere oranla daha avantajlı olduğu düşünülmektedir.…”
Section: Gereç Ve Yöntemlerunclassified